Ekstrakurikuler Pramuka terhadap Self-Confidence Siswa Disabilitas Intelektual - Pangestu, M. Robi Aji; Ariyanto, Dedy; Sugihartatik, Sugihartatik (JOEAI (Journal of Education and Instruction), 2025)
This study aims to examine the effect of extracurricular activities, such as Scouting, on the self-confidence of eleventh-grade students with intellectual disabilities at the Branjangan Special Needs School in Jember. The method used was a quantitative study with an experimental approach, namely a pre-experimental design with a one-group pretest-posttest. The results showed that the average score increased from 52% to 80% after treatment. This study provides new insights into integrating extracurricular activities into vocational education and the importance of an adaptive approach for students with special needs. The conclusions of this study are expected to serve as a model for implementing extracurricular activities in the context of inclusive education.   Keywords: Mild Intellectual Disability, Scouting Extracurricular Activities, Inclusive Education, Vocational Education, Self-Confidence